2001
DOI: 10.1128/iai.69.12.7610-7615.2001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Adenine Methylase Is Essential for Viability and Plays a Role in the Pathogenesis of Yersinia pseudotuberculosis and Vibrio cholerae

Abstract: Salmonella strains that lack or overproduce DNA adenine methylase (Dam) elicit a protective immune response to different Salmonella species. To generate vaccines against other bacterial pathogens, the dam genes of Yersinia pseudotuberculosis and Vibrio cholerae were disrupted but found to be essential for viability. Overproduction of Dam significantly attenuated the virulence of these two pathogens, leading to, in Yersinia, the ectopic secretion of virulence proteins (Yersinia outer proteins) and a fully prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
184
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(189 citation statements)
references
References 42 publications
4
184
0
Order By: Relevance
“…The attenuation of strains with altered dam expression is apparently due to 'inappropriate' expression of virulence factors that results from the failure of Dam to regulate their transcription (Heithoff et al, 1999). In Salmonella, a similar attenuating effect occurs in dam deletion mutants (Heithoff et al, 1999); mutation of the dam gene is lethal in Y. pseudotuberculosis and V. cholerae (Julio et al, 2001).…”
Section: Mouse Virulence Assaymentioning
confidence: 86%
See 3 more Smart Citations
“…The attenuation of strains with altered dam expression is apparently due to 'inappropriate' expression of virulence factors that results from the failure of Dam to regulate their transcription (Heithoff et al, 1999). In Salmonella, a similar attenuating effect occurs in dam deletion mutants (Heithoff et al, 1999); mutation of the dam gene is lethal in Y. pseudotuberculosis and V. cholerae (Julio et al, 2001).…”
Section: Mouse Virulence Assaymentioning
confidence: 86%
“…Dam-overproducing strains of S. enterica, Y. pseudotuberculosis and V. cholerae are all attenuated (Heithoff et al, 1999;Julio et al, 2001). Similarly, our Dam-overproducing P. multocida strain was attenuated using a mouse model.…”
Section: Mouse Virulence Assaymentioning
confidence: 87%
See 2 more Smart Citations
“…cholerae is a Gram-negative enteric pathogen that causes the diarrhoeal disease cholera (Kaper et al, 1995). DNA adenine methylation has been reported in V. cholerae, and a role of the V. cholerae DNA adenine methyltransferase (Dam) in virulence (Julio et al, 2001) and chromosome replication (Egan & Waldor, 2003) has been demonstrated. Although V. cholerae possesses an efficient Dam-directed mismatch repair pathway (Bera et al, 1989), it lacks homologues of Escherichia coli Dcm and Vsr endonuclease (Bhakat et al, 1999), known to be associated with the very short patch (VSP) repair system.…”
Section: Introductionmentioning
confidence: 99%